Blue and yellow long-period variables in the direction of the Small Magellanic Cloud - Mennickent, R. E. (2006)
Aims. We investigate the nature of a sample of 17 long-term periodic variables in the direction of the Small Magellanic Cloud. Methods. Based on new spectroscopic data, we determined spectral types, radial velocities, absolute magnitudes, and colors for these stars. We present a refined discussion of their OGLE light curves along with an analysis of their 2MASS photometry. Results. Most stars turned out to be B-A giants members of the Small Magellanic Cloud. We find a new interacting eclipsing binary with a period of 184 days and two new early-type ellipsoidal variables. One of our objects is the ROSAT source RX J0058.2-7231. We analyzed 11-years of data for this Be X-ray binary finding that their photometric period varies by ∼4% quasiperiodically, on a time scale of ∼1200 days. We find evidence of multiple photometric periods in 2 Ae-type and 1 late-Be type stars. The case of OGLE00445466-7328029 is especially interesting, as this late-type Be star shows a beating phenomenon primarily caused by two closely-spaced frequencies, 0.05733 c/d (17.44 d) and 0.06347 c/d (15.76 d). Four other emission-line objects show stable long-term periodicities and probably correspond to Be-star binaries. Transient photometric periods are only found in 4 non-emission early-type stars.